2010
DOI: 10.1136/bmj.c785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of school based physical activity programme (KISS) on fitness and adiposity in primary schoolchildren: cluster randomised controlled trial

Abstract: Objective To assess the effectiveness of a school based physical activity programme during one school year on physical and psychological health in young schoolchildren. Design Cluster randomised controlled trial. Setting 28 classes from 15 elementary schools in Switzerland randomly selected and assigned in a 4:3 ratio to an intervention (n=16) or control arm (n=12) after stratification for grade (first and fifth grade), from August 2005 to June 2006. Participants 540 children, of whom 502 consented and present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
602
3
25

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(661 citation statements)
references
References 38 publications
25
602
3
25
Order By: Relevance
“…Intervention studies would be needed to confirm this, particularly as some trials have reported activity increases during PE/games classes but not overall (van Sluijs et al, 2007). On the other hand, a similar more recent finding seemed simply to reflect reduced statistical power for non-specific outcomes like overall activity (Kriemler et al, 2010). Our conclusions are therefore provisional but encouraging, suggesting that interventions increasing time spent in PE/games, school breaks, school/non-school active travel, sport or play may translate into increased overall physical activity.…”
Section: Discussionmentioning
confidence: 90%
“…Intervention studies would be needed to confirm this, particularly as some trials have reported activity increases during PE/games classes but not overall (van Sluijs et al, 2007). On the other hand, a similar more recent finding seemed simply to reflect reduced statistical power for non-specific outcomes like overall activity (Kriemler et al, 2010). Our conclusions are therefore provisional but encouraging, suggesting that interventions increasing time spent in PE/games, school breaks, school/non-school active travel, sport or play may translate into increased overall physical activity.…”
Section: Discussionmentioning
confidence: 90%
“…So it can be concluded, physical education should be an important part of that physical activity time. The results of many studies (5,16,18,19,23) on the impact of physical education on the different aspects of people's lives, focused on improving curricula, increasing the number of physical education classes, physical education teacher development, and .... As noted, physical activity can have positive effects on physical and mental, for example, the impact of physical activity on self-concept, quality of life, academic performance and career.…”
Section: Introductionmentioning
confidence: 99%
“…Allerdings muss die Intervention gezielt geplant und durchgeführt werden, damit sie Wirkungen auf Gesundheitsparameter hat (Tittlbach et al 2010). 2 Stunden zusätzlich pro Woche, dazu Bewegungspausen und "sportliche Hausaufgaben", führten in einer Schweizer Studie (Kriemler et al 2010) zu einer Verbesserung der körperlichen Fitness sowie zu einer Verbesserung von Risikofaktoren für Herz-Kreislauf-Erkrankungen.…”
Section: Körperliche Aktivität Einfluss Auf Den Gewichtsstatusunclassified